Yolk@Wrinkled-double shell smart nanoreactors: new platforms for mineralization of pharmaceutical wastewater - Habibi Zare, Masoud; Mehrabani-Zeinabad, Arjomand (Frontiers in Chemistry, 2023)
Nanomaterials with "yolk and shell" structure" can be considered as "nanoreactors" that have significant potential for application in catalysis. Especially in terms of electrochemical energy storage and conversion, the nanoelectrode has a large specific surface area with a unique yolk@shell structure, which can reduce the volume change of the electrode during the charging and discharging process and fast ion/electron transfer channels. The adsorption of products and the improvement of conversion reaction efficiency can greatly improve the stability, speed and cycle performance of the electrode, and it is a kind of ideal electrode material. In this research, heterojunction nanoreactors (FZT Y@WDS) Fe3O4@ZrO2-X@TiO2-X were firstly synthesized based on the solvothermal combined hard-template process, partial etching and calcination. The response surface method was used to determine the performance of the FZT Y@WDS heterojunction nanoreactors and the effects of four process factors: naproxen concentration (NAP), solution pH, the amount of charged photocatalyst, and the irradiation time for photocatalytic degradation of NAP under visible light irradiation. To maximize the photocatalytic activity, the parameters of the loaded catalyst, the pH of the reaction medium, the initial concentration of NAP, and the irradiation time were set to 0.5 g/L, 3, 10 mg/L, and 60 min, respectively, resulting in complete removal of NAP and the amount The optimum was calculated to be 0.5 g/L, 5.246, 14.092 mg/L, and 57.362 min, respectively. Considering the promising photocatalytic activity of FZT Y@WDS under visible light and the separation performance of the nanocomposite, we proposed this photocatalyst as an alternative solution for the treatment of pharmaceutical wastewater.